Labour market power and the distorting effects of international trade - Matthias Mertens (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2018)
This article examines how trade shocks shape labour market imperfections that create market power in labour markets and prevent an efficient allocation of labour. I develop a framework for measuring such labour market distortions in monetary terms and document large degrees of those distortions in Germany's manufacturing sector. Import competition can only exert labour market disciplining effects when firms rather than workers have labour market power. Otherwise, export demand and import competition shocks tend to fortify existing distortions by amplifying labour market power structures. This diminishes the gains from trade compared to a model with perfectly competitive labour markets.
urn:nbn:de:gbv:3:2-97170
Keywords: D24; F14; F16; J50; L13; L60; 330; international trade; market power; labour markets; allocative efficiency